ANALYSIS OF PARENTS' DECISION FACTORS IN CHOOSING THEIR CHILDREN'S EDUCATION AT ALBANNA SENIOR HIGH SCHOOL, DENPASAR - Nabilla Putri; Jumari Jumari; Imam Muhayat (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The background to this research is that, based on the location of Denpasar, where so many Islamic schools have been established, an in-depth study is needed to determine parents' decisions in choosing SMA Albanna Denpasar, located at Jalan Tukad Badung XII B, Renon, South Denpasar, Denpasar City, Bali. This study also examines whether parents achieve satisfactory results after choosing SMA Albanna Denpasar. The objectives of this research are to determine: 1) the factors influencing parents' decisions in choosing SMA Albanna Denpasar for their children; and 2) the factors that contribute most to parents' decisions in choosing SMA Albanna Denpasar for their children. The research method used is descriptive statistics with an exploratory approach. Data collection techniques include observation, questionnaires, and documentation. The results of this study are presented numerically. The results of this study are: 1) Two dominant factors were identified that influenced parents' decisions in choosing SMA Albanna Denpasar: institutional performance (explaining 45.883% of the variance) and service quality (explaining 8.022% of the variance). 2) Within the institutional performance factor, the consistency of the implementation of Islamic values (the highest loading factor: 0.742) was the primary consideration for parents, while within the service quality factor, teacher competence (the highest loading factor: 0.818) had the greatest influence.